Skin Prick Test Positivity in Chronic Urticaria - Koirala, Soniya; Paudel, Upama; Pokhrel, Dinesh Binod; Parajuli, Sudip (Journal of Nepal Health Research Council, 2021)
Background: Skin prick tests identify allergens for chronic urticaria. The objective of this study was to determine skin prick test positivity in patients with chronic urticaria visiting skin outpatient department in one of the tertiary referral centre of Nepal. Methods: This was a hospital based cross-sectional study conducted at Department of Dermatology and Venereology, Tribhuvan University Teaching Hospital. All patients of chronic urticaria aged more than 16 years were taken into study and were prick tested with seven groups of 21 allergens, taking normal saline as negative control and histamine as positive control as per the standard protocol by the Global Allergy and Asthma European Network. Frequency of positivity to each allergen was assessed. Results: Out of 62 patients of chronic urticaria enrolled in the study, 52% were females and 48% were males. Overall, 71% were positive for at least one allergen. The most common allergens which tested positive included Dermatophagoides farinae (50%), Cotton dust (17.7%), Mosquito (16%), hay dust (14.5%), Cladosporium herbarum (14.5%), Candida albicans (12.9%), Parthenium hysterophorus (9.6%), House fly (9.6%), Soya bean (9.6%) and fish sardine (8%). Out of all these patients, 55% patients showed positivity to more than one allergens. Conclusions: A significant proportion of cases with chronic urticaria demonstrated sensitivity to various allergens. Skin prick test can be considered as important diagnostic procedure in cases of chronic urticaria in our population. Keywords: Allergen; dermatophagoides farinae; prick test; urticaria